Prenatal diagnosis of midgut volvulus by fetal MRI: a retrospective study - Kou, Chenguang; Song, Yanfang; Gao, Duo; Zhou, Lixia (Frontiers in Pediatrics, 2024)
BACKGROUND: Fetal midgut volvulus is a rare disease, with high risk of potentially life threatening fetal complications.The aim of this study was to retrospectively analyze the imaging findings of fetal midgut volvulus diagnosed by MRI and explore its value in non-invasive prenatal diagnosis.Retrospective collection of 156 fetuses suspected of intestinal obstruction by ultrasound examination in our hospital. All ultrasound examinations showed fetal intestinal dilation, and fetal MRI diagnosis suspected midgut volvulus in 32 cases(32/156), of which 18 cases(18/32) underwent surgical treatment in neonatal period were confirmed to have midgut volvulus. MRI imaging signs in the 18 fetuses with midgut volvulus were analyzed.During MRI examination, all the 18 fetuses showed gastric and/or intestinal dilatation, most of which showed different degree of obstruction in T1WI and T2WI, showing 'black and white sign' (14/18), 'whirlpool sign' (10/18) and 'coffee beans sign' (6/18). High signal changes in DWI sequence were observed in intestinal tubes with ischemia and infarction. Direct signs of vascular torsion were observed in some cases (8/18). MRI imaging signs indicated fetal midgut volvulus with hydramnios (16/18), meconium pseudocyst (7/18), meconium peritonitis (4/18), testicular hydrocele (3/18), and secondary pulmonary dysplasia (6/18). The operation confirmed the diagnosis of segmental midgut volvulus in 15 cases, complete midgut volvulus in 3 cases, and combined with intestinal atresia in 8 cases.Prenatal MRI plays an important role in the diagnosis of fetal midgut volvulus and the discovery of its complications, which can guide the treatment after birth and provide reference for the prognosis.